Colorectal Cancer Metastasis to the Thymus Gland: Rare Presentation of Colorectal Cancer as Anterior Mediastinal Mass - H. Charles Peters; Xiuli Liu; Atif Iqbal; Lisa A. Cunningham; Sanda A. Tan (Case Reports in Surgery)
Despite improved screening modalities, 15–25% of newly diagnosed colorectal cancers are metastatic at the time of diagnosis. The vast majority of these cases present as hepatic metastasis; however, 22% present with concomitant extrahepatic disease. The thymus gland is an uncommon site of metastasis for any primary malignancy, particularly, colorectal cancer given its vascular and lymphatic drainage. This case report details our experience with a rare case of colorectal cancer metastasis to the thymus gland presenting as a symptomatic mediastinal mass.